LOCAL WINDS, THUNDERSTORMS AND THEIR PERCEIVED EFFECTS ON SOME FARMING ACTIVITIES IN LOKOJA AREA, KOGI STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
This study analysed some characteristics of local winds, thunderstorms and their perceived effects on some farming activities in Lokoja area.  The objectives were to; determine the prevailing local winds, determine some characteristics of local winds and thunderstorms and to assess their perceived effects on some farming activities in Lokoja area. Both primary and secondary data were used. The secondary data was obtained from Nigerian Meteorological Agency, while the primary data was obtained through the administration of 150 questionnaire to farmers in some settlements in Bassa, Lokoja, Ajaokuta, Kogi and Adavi LGAs. The Beaufort Wind scale was used to categorise the local winds. Also Thunderstorm Spectrum was used in classifying the thunderstorms. Results show the wind directions that dominated in Lokoja area as  S/W and  N/E with  mean speed of 1.858 and 1.122 respectively. Results further indicated local winds of Lokoja as calm. It was found out that the thunderstorms fall within range of 1000-2500 J/kg with a mean of 1221.4 J/kg. This places the category of thunderstorms under ordinary with some pulse severe. However the thunderstorms cannot be dissociated from the Multicell types being at the boundary between the two. Some of the perceived effects of local winds include damages to stalks of plants, dropping of unripe fruits amongst others. The advantages of early thunderstorm include, making the soil easy for tillage and ready for seed planting, while its disadvantages include dumping of dried leaves on farm sites, surface run off leading to flash floods and so on.
Keywords: Effects, Farming, Local Winds, Perceived, Thunderstorms